2002
DOI: 10.1063/1.1453339
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domains in epitaxial nanomagnets with uniaxial or fourfold crystal anisotropy

Abstract: In order to prepare submicron sized particles with strong magnetocrystalline anisotropies high quality epitaxial bcc-Fe films were grown on GaAs(110) and GaAs(001) by molecular beam epitaxy. Whereas Fe(110) on GaAs(110) is a model system with uniaxial in-plane anisotropy, Fe(001) on GaAs(001) has a strong fourfold anisotropy for films thicker than ∼5 nm. Various shapes like circular, square, or rectangular elements with sizes from 200 nm up to 6 μm were fabricated by electron beam lithography and ion beam etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…2c and d was observed in long permalloy bars magnetized along the short axis ( [32] Fig. 4b, middle image), but the reference [32] does not provide the explanation on the magnetization configuration of the elements.…”
Section: Magnetic Configurations Of Cobalt Microbars In Demagnetized mentioning
confidence: 84%
“…2c and d was observed in long permalloy bars magnetized along the short axis ( [32] Fig. 4b, middle image), but the reference [32] does not provide the explanation on the magnetization configuration of the elements.…”
Section: Magnetic Configurations Of Cobalt Microbars In Demagnetized mentioning
confidence: 84%
“…Epitaxial Fe films were grown on the A-plane of sapphire Al 2 O 3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) with a Mo seed layer 10 nm thick by pulsed laser deposition in ultrahigh vacuum. The thickness of Fe (011) films was 60 nm and was controlled with a profilometer.…”
Section: Sample Preparation and Measurementsmentioning
confidence: 99%
“…Therefore, microstructures fabricated on the basis of iron exhibit another sequence of magnetic states at the size decrease. Microstructures in the form of strips, rectangles and rectangles with sharpened ends fabricated on the basis of epitaxial Fe (001) and Fe (011) films were studied in [10][11][12][13][14][15][16]. It was found that micromagnetic states and mechanisms of magnetization reversal in microstructures with a lateral size smaller than 50 mm differ from those in film structures [10].…”
Section: Introductionmentioning
confidence: 96%
“…Whereas the effect of the physical shape of the element has been well studied [1-3] the role of the magnetic anisotropy has not been so extensively investigated [3][4][5]. In general, the effect of the magnetic anisotropy is to restrict the states with flux closure to those compatible with local domains pointing along the easy direction axis.…”
mentioning
confidence: 99%